Ideologi Islam Tradisionalis Dalam Tafsir - Asep Mulyaden (UIN Sunan Gunung Djati Bandung, 2021)
Indonesian Islam consists of various groups and organizations, including Traditional Islam or a group that combines Islamic teachings with local customs and Islamic customs throughout the world. This study aims to identify the interpretation of traditional Islamic ideology from relevant references. It used a qualitative method, collected primary and secondary data from the literature study, and explained them through the descriptive analysis method. The results showed that some of the Traditional Islamic Groups are members of the Nahdlatul Ulama organization and others. They have unique characteristics, including exclusive and not accept others’ opinions outside the group. This group has a powerful network and spreads to remote areas through Pondok pesantren. The spread began with the entry of Islam to Indonesia in Sumatra, especially Aceh, and in Java through Wali Songo. Then, it produced great ulama who spread throughout the remote area and founded pesantren or Islamic boarding schools. They spread traditional Islamic teachings through oral and written in the pesantren. They published many written works in the religious field covering fiqh, Sufism, tasawuf, and tafsir. They had two learning methods, namely sorogan and bandungan. At first, in learning tafsir, they only used because as teachers and very simple pass it on. They thought that appreciating classic works is an appreciation of tradition. But after getting a lot of criticism from the reformists (modernists), they began to expand the teachings to various tafsir and wrote more about it. In writing tafsir, they often involve the traditionalist ideology based on Islam Aswaja (Ahlu Sunnah Waljamaah). They wrote about Aswaja's interests in the tafsir, especially as rebuttals to reformist groups, both in the fields of fiqh, tauhid, and tasawuf as contained in the tafsir of KH. Ahmad Sanusi.